2020
DOI: 10.1016/j.sjbs.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between cigarette & shisha smoking and the severity of polycythemia: A cross sectional study

Abstract: Tobacco cigarette smoking is assumed to be a key reason of death all over the world. Smoking had both severe as well long-lasting effects on hematological constraints. As per the data available from World Health Organization, every year nearly 5 million individuals die around the world due to the diseases triggered by smoking. Cigarette smoking is linked with an elevated risk of cardiovascular diseases. To examine the association between shisha or cigarette smoking and the severity of polycythemia, present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
2
7
0
1
Order By: Relevance
“…Hookah has already been recognized as a stimulant of HGB production due to induced hypoxemia, [ 38 ] and the lower prevalence of anemia among hookah smokers in our study may be attributed to this reason. This result is also consistent with a study conducted in Taif city in Saudi Arabia, which was found that shisha or cigarette smoking cause increased HGB levels and secondary polycythemia [ 39 ]. Although the cigarette smoking contributed to the same correlation in univariate analysis, it was not found significant in multivariate model.…”
Section: Discussionsupporting
confidence: 92%
“…Hookah has already been recognized as a stimulant of HGB production due to induced hypoxemia, [ 38 ] and the lower prevalence of anemia among hookah smokers in our study may be attributed to this reason. This result is also consistent with a study conducted in Taif city in Saudi Arabia, which was found that shisha or cigarette smoking cause increased HGB levels and secondary polycythemia [ 39 ]. Although the cigarette smoking contributed to the same correlation in univariate analysis, it was not found significant in multivariate model.…”
Section: Discussionsupporting
confidence: 92%
“…The significant increase in Hb in smokers is correlated with previous studies [10,13]. An increase in hemoglobin concentration is believed to be mediated by exposure to carbon monoxide, and that the increase in Hb in smokers is a compensatory mechanism.…”
Section: Impact Of Smoking On Oxidative Stress and Hematological Parameterssupporting
confidence: 81%
“…Various studies have also suggested that the continuous cigarette smoking has a serious negative impact on hematological parameters such as complete blood cell count, differential count, and endothelial dysfunction [10][11][12]. These effects may be linked to higher risks of developing early atherogenesis, chronic obstructive pulmonary disease, and/or cardiovascular diseases (CVDs) [12,13]. Moreover, non-communicable diseases are the major cause of mortality (73%) in Saudi Arabia, where 37% of deaths are accounted by CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…As a response to the hypoxic status, there is an increase in the hematological parameters. As reported in several studies, cigarette smoking causes an elevated level of hemoglobin [11,[13][14][15], hematocrit [11,15], mean corpuscular volume (MCV) [13,15], and mean corpuscular hemoglobin concentration [13]. It can also cause an elevated level of white blood cells, especially in the sequence of immune responses due to alveolar tissue inflammation and vascular injury [13].…”
Section: Discussionmentioning
confidence: 92%